Kecakapan Bermedia Sosial Bagi Mahasiswa Kesehatan - Leuape, Emanuel Sowe; Silvania S.E Mandaru; Emanuel Sowe Leuape (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
. The Midwifery Department of the Kupang Health Polytechnic (Poltekes) is a vocational educational institution responsible for educating human resources so that they will have medical competencies in their fields. Most of the teaching and learning activities are integrated with the use of digital media devices. The problem is, most local students do not have adequate social media literacy skills. Of course, this has the potential to cause misuse or negligence while using social media. Therefore, the Community Service Team provided digital media literacy training for students of the Midwifery Department of Poltekes - Kupang. The Community Service implementation method consists of two forms: material presentation and practicum (simulation). Evaluation of the measurement of the impact of activities via the One-Group Pretest-Posttest Design method with Time Comparison data analysis techniques. Community Service activities successfully honed local students' skills in utilizing social media both in the context of learning and in their daily activities. Among them: a higher antipathy to negative content (94%), a decrease in social media dependence (25%), and a high level of regulatory literacy (68%). The substance of this Community Service activity should be a provision and guideline for local students so that they are more capable and wise when using social media, especially for learning purposes.